Techno-nationalism and techno-globalism conflict and cooperation - Ostry, Sylvia A.; Nelson, Richard R. 1930- (Integrating national economies, 1995)
Because governments increasingly believe that long-term wealth creation depends on superior technical skills, they are inclined to provide direct or indirect assistance to potential technological winners. This raises the risk of trade and subsidy wars